Perancangan dan Implementasi Sistem Energi Mandiri Hibrid Sel Surya- PLN untuk Mendukung Server Sekolah di Pondok Pesantren Khairul Ummah 2 Pekanbaru - Suwitno, Suwitno; Sandhyavitri, Ari; Sukma, Dian Yayan; Tampubolon, Ari; Kuliz, Muhammad Fakhri Al; Ramadhan, Muhammad Zahrul Faizi; Julianto, Ryan (Unri Conference Series: Community Engagement, 2024)
Khairul Ummah 2 Islamic Boarding School in Pekanbaru Indonesia faced challenges in maintaining its school server operations due to an unstable electricity supply from the state-owned electricity company (PLN). These power fluctuations resulted in hardware damage and disruptions to the academic management system. A hybrid standalone energy system combining solar panels and PLN electricity was designed and implemented to address this issue. The objective was to provide a stable and sustainable energy source to support the school server, which manages academic and administrative data on a cloud computing platform. The methodology involved feasibility studies, system design, equipment procurement, technical installation, and system performance monitoring and evaluation. The implementation results demonstrated that the solar panel system successfully reduced reliance on PLN, increased energy efficiency, and ensured server operation continuity. Evaluations also indicated that the system reduced server downtime by up to 80% and provided several hours of stable electricity during power outages. Implementing the solar-PLN hybrid standalone energy system at Khairul Ummah 2 Boarding School successfully enhanced the stability of the academic management system and reduced electricity-related operational costs. This system is expected to serve as a model for similar technology applications in other educational institutions.